2017
DOI: 10.1186/s12884-017-1578-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the policy of allowing a female labor companion feasible in developing countries? Results from a cross sectional study among Sri Lankan practitioners

Abstract: BackgroundCompanionship during labor is known to have both physical and psychosocial benefits to mother and baby. Sri Lanka made a policy decision to allow a labour companion in 2011. However, implementation has been unsatisfactory. Given the leading role Obstetricians play in the implementation of policy, a study was undertaken to assess the knowledge, attitudes and practices among them.MethodA descriptive cross sectional study was conducted among consultant obstetricians working in the state hospitals using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…The evident practical support of the birth companion during late pregnancy might have helped the primigravid women to work through their childbirth fears and develop childbirth confidence in line with their sociocultural values and expectations. This finding is similar to the Senanayake et al study that reported on the impact the presence of a birth companion from the mother's social network had on providing support to the woman giving birth [46]. We anticipated minimal changes in terms of birth companion support between the study groups because, in Malawi, the female support person is a prerequisite element for hospital delivery and maternity waiting home admission at a birthing facility, in line with the BP/CR strategy [19].…”
Section: Discussionsupporting
confidence: 81%
“…The evident practical support of the birth companion during late pregnancy might have helped the primigravid women to work through their childbirth fears and develop childbirth confidence in line with their sociocultural values and expectations. This finding is similar to the Senanayake et al study that reported on the impact the presence of a birth companion from the mother's social network had on providing support to the woman giving birth [46]. We anticipated minimal changes in terms of birth companion support between the study groups because, in Malawi, the female support person is a prerequisite element for hospital delivery and maternity waiting home admission at a birthing facility, in line with the BP/CR strategy [19].…”
Section: Discussionsupporting
confidence: 81%
“…Another study done to understand the feasibility of engaging birth companions within the health facilities of developing countries, showed 58.8 % of obstetricians did not allow labor companions in their wards [11]. The reasons mentioned for this practice were similar to the hindrances described in our study.…”
Section: Discussionsupporting
confidence: 72%
“…The questionnaire is adopted from a similar study that was conducted in Sri Lanka. [11] In-depth interview was undertaken by the principal investigator, KG, among 3 midwives and 4 residents who were working in the labor ward during the study period. The interviewer used interview guide.…”
Section: Data Collectionmentioning
confidence: 99%
“…There is evidence that PCMC has not been given enough attention in Sri Lanka’s maternal care system [ 16 – 20 ]. Indeed, despite explicit WHO recommendations for labor companionship as a low-cost intervention to improve labor outcomes [ 16 ] and its inclusion in Sri Lankan national policy [ 17 ], a recent survey highlighted that nearly 60% of consultant obstetricians did not allow labour companions in their wards [ 18 ]. Although few studies have explored the area of mistreatment and abuse of women during pregnancy in south Asia, existing qualitative reports suggest a tendency for discriminatory behavior (such as verbal, emotional and even sexual abuse) and a diffuse normalization of disrespectful and abusive treatment of female patients [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%